Contextual control over expression of fear is affected by cortisol - Van Ast, Vanessa A.; Vervliet, Bram; Kindt, Merel (Frontiers in Behavioral Neuroscience, 2012)
At the core of anxiety disorders is the inability to use contextual information to modulate behavioral responses to potentially threatening events. Models of the pathogenesis of anxiety disorders incorporate stress and concomitant stress hormones as important vulnerability factors, while others emphasize sex as an important factor. However, translational basic research has not yet investigated the effects of stress hormones and sex on the ability to use contextual information to modulate responses to threat. Therefore, the purpose of the present study was threefold: first, we aimed at developing an experimental paradigm specifically capable of capturing contextual modulation of the expression of fear. Second, we tested whether cortisol would alter the contextualization of fear expression. Third, we aimed at assessing whether alterations in contextualization due to cortisol were different for men and women. Healthy participants (n = 42) received placebo or hydrocortisone (20 mg) prior to undergoing a newly developed differential contextual fear-conditioning paradigm. The results indicated that people rapidly acquire differential contextual modulation of the expression of fear, as measured by fear potentiated startle (FPS) and skin conductance responses (SCR). In addition, cortisol impaired the contextualization of fear expression leading to increased fear generalization on FPS data in women. The opposite pattern was found in men. Finally, as assessed by SCR, cortisol impaired differential conditioning in men. The results are in line with models suggesting heightened vulnerability in women for developing anxiety disorders after stressful events.